DAMPAK KESEPIAN DAN STRES AKADEMIK TERHADAP KESEJAHTERAAN PSIKOLOGIS MAHASISWA LUAR JAWA DI PERGURUAN TINGGI DI PURWOKERTO (Universitas Muhammadiyah Purwokerto, Universitas Jenderal Soedirman, dan UIN Prof. K.H. Saifuddin Zuhri Purwokerto) - Wardatun Toyiba Aulia Putri; Rr. Setyawati; Dinar Sari Eka Dewi; Itsna Nurrahma Mildaeni (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Students from outside the island of Java tend to choose universities located on Java Island. Various factors underlie this choice, such as the quality of education, accreditation, and the desire to explore new experiences in unfamiliar places. This study aimed to examine the effect of loneliness and academic stress on the psychological well-being of students from outside Java studying in Purwokerto. The study utilized a quantitative method with a multiple linear regression approach. The sample consisted of 334 students from outside Java who were currently pursuing higher education in Purwokerto. The analysis results discovered that H1 was accepted, with an F-value of 159.365 and a significance level of 0.000, which was less than 0.05, indicating that loneliness contributed a significant effect on psychological well-being. H2 was accepted, with an F-value of 304.177 and a significance level of 0.000, indicating that academic stress also significantly affected psychological well-being. H3 was accepted, with an F-value of 536.495 and a significance level of 0.000, showing that loneliness and academic stress simultaneously contributed a significant impact on psychological well-being. These findings highlight the importance of addressing both emotional and academic aspects in supporting the mental health of migrant students.